WAITING TIME PRE ANESTESI BERHUBUNGAN DENGAN TINGKAT KECEMASAN PASIEN PRE OPERASI - Agus Sarwo Prayogi; Niken Anggraini Sri Saputri; Ida Mardalena (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2020)
Surgery and anesthesia are invasive and planned treatment procedures. The operation to be performed requires mental preparation on the patient. One form of hospital service quality that patients often complain about is waiting time. Waiting time is synonymous with boredom, anxiety, stress for patients. Purpose : To know the relationship between waiting time pre anesthesia with anxiety levels in general anesthesia patients at the Central Surgical Installation RS PKU Muhammadiyah Yogyakarta. Method : This research is quantitative observational analytic using cross sectional research design. This research was carried out at the Central Surgical Installation RS PKU Muhammdiyah Yogyakarta on January 13-25, 2020. The population of this study was all patients undergoing elective surgery under general anesthesia with 62 patients. Data analysis using Chi Square test.Result : Research shows that the number of respondents with a waiting time pre anesthesia >30 minutes suffered severe anxiety as much as 11 respondents (57.9%). Based on Chi Square test, result of P value 0.004 (< 0.05). Conclusion : There is a relationship between waiting time pre anesthesia with anxiety levels in general anesthesia patients.